Negative electrode material and preparation method and application thereof
By using the negative electrode materials of the core layer composed of carbon-coated tin nanowires and carbon nanotubes and graphene-coated shells in lithium-ion batteries, it is solved that it is difficult for traditional lithium-ion batteries to achieve high specific capacity and cycle simultaneously. The stability issue has achieved efficient improvement in lithium-ion battery performance.
Patent Information
- Application Number
- CN202411298792.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The negative electrode materials of traditional lithium-ion batteries are difficult to achieve high specific capacity and cyclic stability at the same time. The theoretical specific capacity of graphite is limited, while silicon has a decrease in cyclic stability due to volume expansion.
Using a negative electrode material including a core layer and a shell layer, the core layer is composed of carbon-coated tin nanowires and carbon nanotubes. The shell layer is covered with graphene to form a three-dimensional conductive network and a multi-porous structure to alleviate the volume expansion effect of silicon. , and improve the interface stability of solid electrolytes.
It significantly improves the specific capacity and cyclic stability of lithium-ion batteries. Through the conductivity of carbon-coated tin nanowires and carbon nanotubes and the protection of graphene, it realizes efficient lithium-ion transmission and volume expansion buffering of silicon materials. .
Smart Images

Figure CN118825248B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] Due to the rapid development and widespread application of portable electronic devices and electric vehicles, there is an urgent need for lithium-ion batteries with high specific energy and long cycle life. Currently, commercial lithium-ion batteries mainly use graphite as the negative electrode material. However, since the theoretical specific capacity of graphite is only 372mAh / g, the further improvement of the specific energy of lithium-ion batteries is limited. Silicon has attracted great attention from researchers because of its extremely high theoretical lithium insertion specific capacity (up to 4200mAh / g) and low lithium storage potential. It is one of the ideal candidate materials for high-capacity lithium storage materials. However, the volume expansion of silicon exceeds 300% during the lithium storage process, which easily causes the pulverization of silicon particles, causing the active material to fall off from the current collector, resulting in a significant decrease in the cycle stability of the electrode. That is, it is difficult for traditional negative electrode materials to make the battery have both high specific capacity and cycle stability. Summary of the invention
[0003] Based on this, it is necessary to provide a negative electrode material and a preparation method and application thereof. The negative electrode material of the present application can simultaneously enable the battery to have a higher specific capacity and cycle stability.
[0004] In a first aspect, the present application provides a negative electrode material, comprising a core layer and a shell layer; the shell layer covers the core layer; the material of the core layer comprises silicon material, carbon nanotubes and carbon-coated tin nanowires, and the carbon-coated tin nanowires and the carbon nanotubes are attached to the surface of the silicon material; the material of the shell layer comprises graphene.
[0005] In some embodiments, the particle size of the negative electrode material is 0.2 μm to 5 μm.
[0006] In some embodiments, D50 of the negative electrode material is 1 μm to 4 μm.
[0007] In some embodiments, the silicon material includes a coating material and a silicon-based material, and the coating material coats the silicon-based material; the silicon-based material includes at least one of silicon, silicon monoxide and a silicon alloy, and the coating material includes at least one of carbon, oxide and organic matter.
[0008] In some embodiments, the silicon material includes at least one of a flaky silicon-based material, a granular silicon-based material, and a linear silicon-based material.
[0009] In some embodiments, the carbon-coated tin nanowires have a diameter of less than 100 nm.
[0010] In some embodiments, the carbon-coated tin nanowires have an aspect ratio of 5-1000.
[0011] In some embodiments, the carbon nanotube has a diameter of less than 20 nm.
[0012] In some embodiments, the aspect ratio of the carbon nanotubes is 10-1000.
[0013] In some embodiments, the shell layer has a thickness of 1 nm to 100 nm.
[0014] In some embodiments, the mass percentage of silicon element is 70% to 98%, the mass percentage of tin element is 0.5% to 20%, and the mass percentage of carbon element is 1.5% to 20% based on the mass percentage of the negative electrode material.
[0015] In a second aspect, the present application provides a method for preparing a negative electrode material according to any one of the above items, comprising the following steps:
[0016] Dispersing carbon nanotubes, silicon material, dispersant and dispersion medium to obtain a first composite precursor;
[0017] Dispersing the tin source, graphene and a dispersion medium to obtain a second composite precursor;
[0018] The first composite precursor and the second composite precursor are mixed and then sintered in a mixed atmosphere of a protective gas and a carbon source to obtain a negative electrode material.
[0019] In a third aspect, the present application provides a negative electrode plate, comprising a current collector and an active layer located on the surface of the current collector, wherein the active layer comprises any of the negative electrode materials described above or a negative electrode material prepared by the negative electrode material preparation method described above.
[0020] In a fourth aspect, the present application provides a secondary battery, comprising the above-mentioned negative electrode plate.
[0021] In a fifth aspect, the present application provides an electrical device comprising the above-mentioned secondary battery.
[0022] In the above-mentioned negative electrode material, the carbon-coated tin nanowires and carbon nanotubes in the core layer can form a three-dimensional conductive network. At the same time, the carbon-coated tin nanowires and carbon nanotubes themselves have a certain length and good softness and elasticity. The carbon-coated tin nanowires can maintain the integrity and consistency of the structure during the charge and discharge process, and can also achieve good electrical contact between the negative electrode active materials. At the same time, tin has excellent ionic conductivity, and carbon nanotubes have excellent electronic conductivity, which can greatly improve the conductivity of the negative electrode material, and utilize the high specific capacity characteristics of silicon materials to make the battery have a higher specific capacity. Further, the carbon-coated tin nanowires, carbon nanotubes and graphene in the negative electrode material can form a three-dimensional cross-linked network and a multi-microporous structure, providing a transmission channel for lithium ions and a buffer space for the volume expansion of silicon materials, and alleviating the volume effect of silicon materials in the process of lithium extraction. Further, graphene, as a protective layer of the shell layer, that is, the core layer, can also form a stable solid electrolyte interface film on the surface of the negative electrode material, thereby improving the cycle stability of the battery. The negative electrode material of the present application can have both high specific capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] FIG1 is a partial schematic diagram of a negative electrode material provided in one embodiment of the present application;
[0024] FIG2 is a scanning electron microscope image of the core layer of the negative electrode material in Example 1 of the present application;
[0025] FIG3 is a scanning electron microscope image of the negative electrode material particles in Example 1 of the present application.
[0026] 10. Silicon materials; 20. Carbon-coated tin nanowires; 30. Carbon nanotubes; 40. Graphene. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0029] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0030] As shown in Figure 1, an embodiment of the present application provides a negative electrode material, including a core layer and a shell layer; the shell layer covers the core layer; the material of the core layer includes silicon material 10, carbon nanotubes 30 and carbon-coated tin nanowires 20, and the carbon-coated tin nanowires 20 and the carbon nanotubes 30 are attached to the surface of the silicon material 10; the material of the shell layer includes graphene 40.
[0031] In the above-mentioned negative electrode material, the carbon-coated tin nanowires 20 and carbon nanotubes 30 in the core layer can form a three-dimensional conductive network. At the same time, the carbon-coated tin nanowires 20 and carbon nanotubes 30 themselves have a certain length and good softness and elasticity. The carbon-coated tin nanowires 20 can maintain the integrity and consistency of the structure during the charge and discharge process, and can also achieve good electrical contact between the negative electrode active materials. At the same time, tin has excellent ionic conductivity, and carbon nanotubes 30 have excellent electronic conductivity, which can greatly improve the conductivity of the negative electrode material, and utilize the high specific capacity characteristics of the silicon material 10 to make the battery have a higher specific capacity. Further, the carbon-coated tin nanowires 20, carbon nanotubes 30 and graphene 40 in the negative electrode material can form a three-dimensional cross-linked network and a multi-microporous structure, providing a lithium ion transmission channel and a buffer space for the volume expansion of the silicon material 10, and alleviating the volume effect of the silicon material 10 during the lithium extraction process. Furthermore, the graphene 40 as a protective layer of the shell layer or the core layer can also form a stable solid electrolyte interface film on the surface of the negative electrode material, thereby improving the cycle stability of the battery. The negative electrode material of the present application can have both high specific capacity and cycle stability.
[0032] It can be understood that the carbon-coated tin nanowires 20 and carbon nanotubes 30 attached to the surface of the silicon material 10 means that the carbon-coated tin nanowires 20 and carbon nanotubes 30 can be connected to the surface of the silicon material 10 through their ends, or can be attached to the surface of the silicon material 10 by winding. Among them, the carbon-coated tin nanowires 20 can be in-situ reduced on the surface of the silicon material 10, and the graphene 40 can be reduced graphene oxide 40.
[0033] In some embodiments, the material of the shell layer is graphene 40 , and the graphene 40 entirely covers the carbon-coated tin nanowires 20 , the carbon nanotubes 30 , and the silicon material 10 .
[0034] The graphene 40 integrally covers the carbon-coated tin nanowires 20, the carbon nanotubes 30 and the silicon material 10, which means that the carbon-coated tin nanowires 20, the carbon nanotubes 30 and the silicon material 10 are connected to form a whole, and the graphene 40 then integrally covers the whole.
[0035] In some embodiments, the particle size of the negative electrode material is 0.2 μm to 5 μm.
[0036] It is understandable that the particle size of the negative electrode material is related to the plane size of the flaky silicon-based material. Within the particle size range of the above-mentioned negative electrode material, the shell layer can achieve a good coating effect on the core layer. When the particle size of the negative electrode material is too large, that is, the plane size of the flaky silicon-based material is large, it will be difficult to achieve a good coating effect of the shell layer on the core layer. At the same time, the volume expansion of the flaky silicon-based material during the charging and discharging process will be too large, affecting the cycle stability of the negative electrode material. Optionally, the particle size of the negative electrode material is 0.2μm, 0.4μm, 0.6μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm. Alternatively, the particle size of the negative electrode material can also be within the range between any two of the above-mentioned particle sizes.
[0037] In some embodiments, the D50 of the negative electrode material is 1 μm to 4 μm.
[0038] Optionally, the D50 of the negative electrode material is 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm. Alternatively, the D50 of the negative electrode material may also be within the range between any two of the above particle sizes.
[0039] In some embodiments, the silicon material 10 includes a coating material and a silicon-based material, wherein the coating material coats the silicon-based material; the silicon-based material includes at least one of silicon, silicon monoxide and a silicon alloy, and the coating material includes at least one of carbon, oxide and organic matter.
[0040] Optionally, the silicon alloy includes at least one of silicon-aluminum alloy, silicon-magnesium alloy and silicon-ferroalloy.
[0041] In some embodiments, the silicon material 10 includes at least one of nanosheets, particles, and nanowires.
[0042] It is to be understood that the above-mentioned nanosheet refers to a sheet-like material with a thickness in the nanometer size.
[0043] In some embodiments, the silicon-based material includes at least one of a sheet-like silicon-based material, a granular silicon-based material, and a linear silicon-based material.
[0044] In some of the embodiments, the thickness of the sheet-like silicon-based material is 5 nm to 500 nm.
[0045] Optionally, the thickness of the flaky silicon-based material is 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 50 nm, 60 nm, 80 nm, 100 nm, 150 nm, 200 nm, 300 nm, 400 nm or 500 nm. Alternatively, the thickness of the flaky silicon-based material may also be within a range between any two of the above thicknesses.
[0046] In some of the embodiments, the planar size of the flaky silicon-based material is 100 nm to 2000 nm.
[0047] It is understood that the plane size of the flaky silicon-based material refers to the distance between the two farthest points in the projection of the flaky silicon-based material on the horizontal plane. Optionally, the plane size of the flaky silicon-based material is 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm or 2000nm. Alternatively, the plane size of the flaky silicon-based material may also be within the range between any two of the above sizes.
[0048] In some embodiments, the diameter of the carbon-coated tin nanowires 20 is less than 100 nm.
[0049] Optionally, the diameter of the carbon-coated tin nanowire 20 is 5 nm to 100 nm. Further optionally, the diameter of the carbon-coated tin nanowire 20 is 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm. Alternatively, the diameter of the carbon-coated tin nanowire 20 may also be within the range between any two of the above diameters.
[0050] In some embodiments, the carbon-coated tin nanowires 20 have an aspect ratio of 5-1000.
[0051] Optionally, the aspect ratio of the carbon-coated tin nanowires 20 is 5, 10, 20, 50, 100, 150, 200, 300, 400, 500, 600, 700, 800, 850, 900, 950 or 1000. Alternatively, the aspect ratio of the carbon-coated tin nanowires 20 may also be within the range between any two of the above aspect ratios.
[0052] In some embodiments, the diameter of the carbon nanotubes 30 is less than 20 nm.
[0053] Optionally, the diameter of the carbon nanotube 30 is 1 nm to 20 nm. Further optionally, the diameter of the carbon nanotube 30 is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm. Alternatively, the diameter of the carbon nanotube 30 may also be within the range between any two of the above diameters.
[0054] In some embodiments, the aspect ratio of the carbon nanotubes 30 is 10-1000.
[0055] Optionally, the aspect ratio of the carbon nanotube 30 is 10, 20, 50, 100, 150, 200, 300, 400, 500, 600, 700, 800, 850, 900, 950 or 1000. Alternatively, the aspect ratio of the carbon nanotube 30 may be within a range between any two of the above aspect ratios.
[0056] In some embodiments, the shell layer has a thickness of 1 nm to 100 nm.
[0057] Within the above-mentioned shell thickness range, the graphene 40 and the carbon-coated tin nanowires 20 and carbon nanotubes 30 form a three-dimensional cross-linked network and a microporous structure with better effect, providing a transmission channel for lithium ions and a buffer space for the volume expansion of the silicon material 10, and having a better effect of alleviating the volume effect of the silicon material 10 during lithium extraction. At the same time, the graphene 40 has a better effect of forming a stable solid electrolyte interface film as a protective layer, thereby improving the cycle stability of the battery. Optionally, the thickness of the shell is 1nm, 2nm, 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm. Alternatively, the thickness of the shell can also be within the range between any two of the above thicknesses.
[0058] In some of the embodiments, based on the mass percentage of the negative electrode material, the mass percentage of silicon is 70% to 98%, the mass percentage of tin is 0.5% to 20%, and the mass percentage of carbon is 1.5% to 20%.
[0059] Optionally, the mass percentage of silicon is 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96% or 98% based on the mass percentage of the negative electrode material. Alternatively, the mass percentage of silicon can also be within the range between any two of the above mass percentages.
[0060] Optionally, the mass percentage of the tin element is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 15%, 17%, 18%, 19% or 20% based on the mass percentage of the negative electrode material. Alternatively, the mass percentage of the tin element may also be within the range between any two of the above mass percentages.
[0061] Optionally, the mass percentage of carbon element is 1.5%, 2%, 3%, 4.5%, 5%, 6%, 7.5%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 19% or 20% based on the mass percentage of negative electrode material. Alternatively, the mass percentage of carbon element can also be within the range between any two of the above mass percentages.
[0062] Another embodiment of the present application provides a method for preparing any of the above negative electrode materials, comprising the following steps:
[0063] Dispersing the carbon nanotubes 30, the silicon material 10, the dispersant and the dispersion medium to obtain a first composite precursor;
[0064] Dispersing the tin source, graphene 40 and a dispersion medium to obtain a second composite precursor;
[0065] The first composite precursor and the second composite precursor are mixed and then sintered in a mixed atmosphere of a protective gas and a carbon source to obtain a negative electrode material.
[0066] Exemplarily, the tin source includes at least one of stannous oxide and tin nanowires. Exemplarily, the carbon source includes one or more of acetylene, ethylene, methane, ethane, propane and n-butane.
[0067] In some embodiments, the sintering temperature is 650°C to 900°C.
[0068] Optionally, the temperature of the sintering process is 650° C., 700° C., 750° C., 800° C., 950° C. or 900° C. Alternatively, the temperature of the sintering process may also be within a range between any two of the above temperatures.
[0069] In some embodiments, the mixed raw material also includes a dispersant.
[0070] In some embodiments, the dispersant includes at least one of polyvinylpyrrolidone (PVP), N-methylpyrrolidone, and carboxymethylcellulose.
[0071] In some embodiments, the method for preparing the negative electrode material comprises the following steps:
[0072] Dispersing the carbon nanotubes 30, the silicon material 10, the dispersant and the dispersion medium, and subjecting the dispersed suspension to sand milling, filtering, washing and drying to obtain a first composite precursor;
[0073] Dispersing the tin source, graphene 40 and the dispersion medium, and subjecting the dispersed suspension to sand milling, filtering, washing and drying to obtain a second composite precursor;
[0074] After the first composite precursor and the second composite precursor are mixed, they are sintered in a mixed atmosphere of a protective gas and a carbon source to obtain a negative electrode material.
[0075] Another embodiment of the present application provides a negative electrode plate, including a current collector and an active layer located on the surface of the current collector, wherein the active layer includes any of the above-mentioned negative electrode materials or a negative electrode material prepared by the above-mentioned method for preparing the negative electrode material.
[0076] Another embodiment of the present application provides a secondary battery, comprising the above-mentioned negative electrode plate.
[0077] Another embodiment of the present application provides an electrical device, comprising the secondary battery described above.
[0078] The following are specific embodiments
[0079] Example 1
[0080] Preparation method of negative electrode material:
[0081] (1) Adding silicon nanosheets with a thickness of 5 nm to 100 nm and a plane size of 100 nm to 2000 nm and PVP to a carbon nanotube 30 solution, the mixture is homogenized and dispersed in a homogenizer, the homogenized suspension is sand-milled in a sand mill, and then filtered, washed, and dried to obtain a uniformly dispersed first composite precursor.
[0082] (2) The tin oxide, graphene 40 and PVP are dispersed in a homogenizer, and then sand-milled in a sand mill. After filtering, washing and drying, a uniformly dispersed second composite precursor is obtained.
[0083] (3) Dry-mixing the first composite precursor and the second composite precursor, and after mixing evenly, placing the mixture into a high-temperature sintering furnace and sintering the mixture from room temperature to 700° C. in a mixed atmosphere of nitrogen and acetylene to obtain a negative electrode material.
[0084] Preparation method of negative electrode sheet:
[0085] The negative electrode material, conductive agent SP, and sodium alginate prepared in this embodiment are mixed in an aqueous solution at a mass ratio of 80%:5%:15% and stirred continuously to obtain a negative electrode slurry. The negative electrode slurry is applied to the surface of the copper foil with a scraper, and then dried to obtain a negative electrode sheet. The negative electrode sheet is cold pressed, and the cold pressed negative electrode sheet is punched to prepare a small disc with a diameter of 15 mm.
[0086] Battery preparation method:
[0087] The negative electrode sheet prepared in this embodiment is paired with a lithium sheet to assemble into a button-type half-cell, and the battery assembly process is carried out in a glove box filled with argon. Celgard2300 membrane is used as an isolation membrane, and the electrolyte is a solution of 1 mol / L LiPF6 dissolved in EC:DMC:FEC (volume ratio 4.8:4.8:0.4).
[0088] Referring to Figures 2 and 3, Figure 3 is a scanning electron microscope image of the negative electrode material particles, that is, graphene 40 as a shell layer covers the carbon-coated tin nanowires 20, carbon nanotubes 30 and silicon material 10 as a whole. Figure 2 is a scanning electron microscope image of the core layer of the negative electrode material. It should be understood that in Figure 2, the carbon-coated tin nanowires 20 and carbon nanotubes 30 are relatively dense, which blocks the silicon material 10. In the silicon material 10 in the negative electrode material prepared in Example 1, the core layer includes flaky nanosilicon and a small amount of granular silicon, and the surface of the silicon material 10 is coated with a dense and uniform carbon coating layer, and there are also carbon-coated tin nanowires 20 and carbon nanotubes 30 dispersed between the silicon materials 10. In the negative electrode material, the mass percentage of silicon element in terms of silicon alone is 86.6%, the mass percentage of tin element in terms of tin alone is 4.6%, the mass percentage of carbon element in terms of the negative electrode material is 5.2%, and the mass percentage of other substances in terms of the negative electrode material is 3.1%.
[0089] Example 2
[0090] Preparation method of negative electrode material:
[0091] The method for preparing the negative electrode material in Example 2 is substantially the same as that in Example 1, the only difference being that the silicon nanosheets in step (1) are replaced by silicon wafer cutting waste.
[0092] The negative electrode sheet and the preparation method and the battery preparation method in Example 2 are the same as those in Example 1.
[0093] Example 3
[0094] Preparation method of negative electrode material:
[0095] The method for preparing the negative electrode material in Example 3 is substantially the same as that in Example 1, the only difference being that the stannous oxide in step (2) is replaced by tin nanowires.
[0096] The negative electrode plate and the preparation method and the battery preparation method in Example 3 are the same as those in Example 1.
[0097] Example 4
[0098] Preparation method of negative electrode material:
[0099] The preparation method of the negative electrode material in Example 4 is basically the same as that in Example 1, the only difference being that the silicon nanosheets in step (1) are replaced by silicon particles with a size of 100 nm to 200 nm, and the stannous oxide in step (2) is replaced by tin nanowires.
[0100] The negative electrode sheet and the preparation method and the battery preparation method in Example 4 are the same as those in Example 1.
[0101] Example 5
[0102] Preparation method of negative electrode material:
[0103] The preparation method of the negative electrode material in Example 5 is basically the same as that in Example 1, the only difference being that the silicon nanosheets in step (1) are replaced by silicon nanowires with a diameter of 50 nm to 100 nm and a length of 100 nm to 2000 nm, and the stannous oxide in step (2) is replaced by tin nanowires.
[0104] The negative electrode sheet and the preparation method and the battery preparation method in Example 5 are the same as those in Example 1.
[0105] Example 6
[0106] Preparation method of negative electrode material:
[0107] The preparation method of the negative electrode material in Example 6 is basically the same as that in Example 1, the only difference being that the silicon nanosheets in step (1) are replaced by silicon dioxide nanosheets, and the stannous oxide in step (2) is replaced by tin nanowires.
[0108] The negative electrode plate and the preparation method and the battery preparation method in Example 6 are the same as those in Example 1.
[0109] Example 7
[0110] Preparation method of negative electrode material:
[0111] The preparation method of the negative electrode material in Example 7 is basically the same as that in Example 1, the only difference being that the silicon nanosheets in step (1) are replaced by silicon oxide particles with a particle size of 5 μm to 10 μm, and the stannous oxide in step (2) is replaced by tin nanowires.
[0112] The negative electrode plate and the preparation method and the battery preparation method in Example 7 are the same as those in Example 1.
[0113] Example 8
[0114] Preparation method of negative electrode material:
[0115] The method for preparing the negative electrode material in Example 8 is substantially the same as that in Example 1, the only difference being that the silicon nanosheets in step (1) are replaced with silicon dioxide particles having a particle size of 5 μm to 10 μm.
[0116] The negative electrode plate and the preparation method and the battery preparation method in Example 8 are the same as those in Example 1.
[0117] Comparative Example 1
[0118] Preparation method of negative electrode material:
[0119] (1) Silicon particles with a particle size of 5 μm to 10 μm, polyvinyl pyrrolidone and PVP are homogenously dispersed in a homogenizer, the homogenized suspension is sand-milled in a sand mill, and then filtered, washed and dried to obtain a uniformly dispersed composite precursor.
[0120] (2) The composite precursor is placed in a high-temperature sintering furnace and sintered from room temperature to 700°C in a mixed atmosphere of nitrogen and acetylene to obtain a negative electrode material.
[0121] The negative electrode sheet and the preparation method and the battery preparation method in Comparative Example 1 are the same as those in Example 1.
[0122] Comparative Example 2
[0123] Preparation method of negative electrode material:
[0124] Silicon oxide with a particle size of 5 μm to 10 μm is homogeneously dispersed in a homogenizer, and then placed in a high-temperature sintering furnace and sintered from room temperature to 700° C. in a mixed atmosphere of nitrogen and acetylene to obtain a negative electrode material.
[0125] The negative electrode sheet and the preparation method and the battery preparation method in Comparative Example 2 are the same as those in Example 1.
[0126] Comparative Example 3
[0127] The preparation method of the negative electrode material in Comparative Example 3 is substantially the same as that in Example 1, the only difference being that graphene is not added in step (1).
[0128] The negative electrode sheet and the preparation method and the battery preparation method in Comparative Example 3 are the same as those in Example 1.
[0129] Comparative Example 4
[0130] The preparation method of the negative electrode material in Comparative Example 4 is substantially the same as that in Example 1, the only difference being that the graphene in step (1) is replaced by carbon black.
[0131] The negative electrode sheet and the preparation method and the battery preparation method in Comparative Example 4 are the same as those in Example 1.
[0132] The batteries prepared in each embodiment and comparative example were tested by the following test method: a blue electric charge and discharge tester was used to perform constant current charge and discharge on the batteries, wherein the cut-off voltage was set to 0.005-1.0V and the rate was set to 0.2C, and the first-week charging capacity, first-week coulomb efficiency, 100th-week charging capacity, and 100th-week coulomb efficiency were tested.
[0133] The 100-week cycle capacity retention rate was calculated using the following formula: 100-week cycle capacity retention rate = 100th week charge capacity / first week charge capacity × 100%.
[0134] The first-week charging capacity, first-week coulombic efficiency, 100th-week coulombic efficiency and 100-week cycle capacity retention rate data of each embodiment and comparative example are shown in Table 1 below:
[0135] Table 1
[0136]
[0137] As can be seen from Table 1, the first-week charging capacity of the negative electrode materials including silicon nanosheets in Examples 1 to 5 is greater than 2500mAh / g, the first-week coulomb efficiency is greater than 87%, and the 100-week cycle capacity retention rate is above 92%. The 100-week capacity retention rate of the negative electrode materials of the conventional carbon-coated silicon material in Comparative Example 1 is less than 60%. For the negative electrode materials including silicon oxide, the 100-week cycle capacity retention rate of the negative electrode materials in Examples 6 to 8 is 45.24%, and the 100-week cycle capacity retention rate of the conventional carbon-coated silicon oxide negative electrode materials in Comparative Example 2 is 65.24%. In Comparative Example 3, graphene is not added to the negative electrode material, and in Comparative Example 4, graphene is replaced with carbon black, and its 100-week cycle capacity retention rate is lower than that of Examples 1 to 5.
[0138] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0139] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A negative electrode material, characterized in that: It comprises a core layer and a shell layer; the shell layer covers the core layer; the material of the core layer comprises silicon material, carbon nanotubes and carbon-coated tin nanowires, and the carbon-coated tin nanowires and the carbon nanotubes are attached to the surface of the silicon material; the material of the shell layer is graphene; The silicon material comprises a coating material and a silicon-based material, wherein the coating material coats the silicon-based material; the silicon-based material comprises at least one of silicon, silicon monoxide and a silicon alloy, and the coating material comprises carbon; The carbon-coated tin nanowires, the carbon nanotubes and the silicon material are connected to form a whole, and the graphene coats the whole.
2. The negative electrode material according to claim 1, characterized in that The particle size of the negative electrode material is 0.2 μm to 5 μm.
3. The negative electrode material according to claim 1, characterized in that The D50 of the negative electrode material is 1 μm to 4 μm.
4. The negative electrode material according to claim 1, characterized in that The silicon-based material includes at least one of a sheet-shaped silicon-based material, a particle-shaped silicon-based material, and a linear-shaped silicon-based material.
5. The negative electrode material according to claim 1, characterized in that The diameter of the carbon-coated tin nanowires is less than 100 nm; and / or, The aspect ratio of the carbon-coated tin nanowires is 5 to 1000; and / or, The diameter of the carbon nanotube is less than 20 nm; and / or, The aspect ratio of the carbon nanotubes is 10 to 1000; and / or, The thickness of the shell layer is 1 nm to 100 nm.
6. The negative electrode material according to any one of claims 1 to 5, characterized in that Calculated by mass percentage of the negative electrode material, the mass percentage of silicon element is 70% to 98%, the mass percentage of tin element is 0.5% to 20%, and the mass percentage of carbon element is 1.5% to 20%.
7. A method for preparing the negative electrode material according to any one of claims 1 to 6, characterized in that: The steps include: Dispersing the carbon nanotubes, silicon material, dispersant and dispersion medium, and subjecting the dispersed suspension to sand milling, filtering, washing and drying to obtain a first composite precursor; Dispersing the tin source, graphene and dispersion medium, and subjecting the dispersed suspension to sand milling, filtering, washing and drying to obtain a second composite precursor; The first composite precursor and the second composite precursor are mixed and then sintered in a mixed atmosphere of a protective gas and a carbon source to obtain a negative electrode material.
8. A negative electrode plate, characterized in that: It comprises a current collector and an active layer located on the surface of the current collector, wherein the active layer comprises the negative electrode material according to any one of claims 1 to 6 or the negative electrode material prepared by the method for preparing the negative electrode material according to claim 7.
9. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 8.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
